CONSTRUCTION OF MOTHERS IDENTITY IN ONLINE COMMUNITY: STUDY OF MEMBERS OF HALO IBU COMMUNITY - Ruvira Arindita; Muchammad Nasucha; Lisa Esti Puji Hartanti; Nursalsa Arifah; Shafiyya Lubna (ASPIRATION Journal, 2021)
Transition to motherhood presents many challenges for women. Negotiating changes and self-identity has become one of the most intriguing ones. During this period, women’s need for information and support increase. ‘Halo Ibu’, the pioneer of the maternal support online community, aims to help women in their transition to motherhood. This research attempts to investigate how mothers’ identity, constructed with the background of their community members as well as to know the role that community, plays in the lives of a mother. The theory used is Mead’s Symbolic Interactionism and the concept of mother identity construction proposed by Laney et al. This is a qualitative study with a constructivist paradigm. This research employed interviews and observation as data gathering processes. The informants were the founder, the content creators, and the coordinator of the community. Results indicated that there was a simultaneous dialectic process between internalization, objectivation, and externalization about the community’s values which are self-love, self-awareness, and non-judgemental support. This process was present during the phase of mother identity construction. Even though it is an online community, the construction of reality regarding community and identity concepts is based on experiences, interactions, and information searched by individuals both online and offline.